2019
DOI: 10.1080/09658211.2019.1646771
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of memory ability in synaesthesia

Abstract: People with synaesthesia have often been reported to possess enhanced memory relative to the general population and, in some cases, exceptional memory ability. However, there are also inconsistencies in this literature and it is unclear whether this reflects sampling error (exacerbated by low Ns) or more meaningful differences that arise because synaesthesia relates to some aspects of memory more than others. To this end, a multi-level meta-analysis was conducted. Synaesthetes have enhanced episodic memory wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 76 publications
0
20
0
Order By: Relevance
“…In a similar vein, Simner et al (2009) later suggested that the cognitive advantages associated with synaesthesia (such as enhanced memory; e.g., Rothen et al, 2012;Ward et al, 2019) might be elevated to prodigious savant levels when combined with the autistic tendency to obsess and overrehearse. That is, each condition contributes different cognitive elements that, when combined, may lead to the emergence of savant skills.…”
Section: Enhanced Cognition and Savant Talentmentioning
confidence: 96%
“…In a similar vein, Simner et al (2009) later suggested that the cognitive advantages associated with synaesthesia (such as enhanced memory; e.g., Rothen et al, 2012;Ward et al, 2019) might be elevated to prodigious savant levels when combined with the autistic tendency to obsess and overrehearse. That is, each condition contributes different cognitive elements that, when combined, may lead to the emergence of savant skills.…”
Section: Enhanced Cognition and Savant Talentmentioning
confidence: 96%
“…As an example, FPT performance is partly dependent on matching the image with representations from memory. Since synesthetes have previously been shown to outperform nonsynesthetes in a wide range of memory tasks (Ward et al, 2019), a better FPT performance in more synesthetic individuals might be driven by memory effects. Further, synesthetes seem to have more vivid visual mental imagery (Ward and Simner, 2020), which likely is also required in the FPT matching process.…”
Section: Visual Perception and Degree Of Synesthesiamentioning
confidence: 99%
“…To aid the interpretation of the findings from native and nonnative discrimination, in Experiment 1 we also included digit span as a control task in which we expected the synesthetes to have no or at most slight superiority (47). If synesthetes show an overall superiority in making both native and nonnative discriminations, the results for digit span will allow us to evaluate whether the differences might arise from higher overall motivation or attentiveness during the experimental session rather than from heightened perceptual sensitivity.…”
Section: Significancementioning
confidence: 99%